The Equivalency Education Package Program as an Effort to Address School Dropout Rates from the Perspective of Islamic Education at PKBM GP Ansor Luwunggede - Tiara Mukhti Nalendri; Salmah Nur Fajriana; Ratoni Ratoni (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the role of the Equivalency Education Package Program in reducing school dropout rates from the perspective of Islamic education at PKBM GP Ansor Luwunggede. Specifically, it examines the implementation of the program, identifies the supporting and inhibiting factors influencing its effectiveness, and explores the integration of Islamic educational values in strengthening learners' academic participation and character development. This study employed a qualitative research design using interviews, participant observation, and documentation as the primary data collection techniques. Data were analyzed through the stages of data reduction, data display, and conclusion drawing to generate a comprehensive understanding of the implementation of the program. The findings indicate that the Equivalency Education Package Program has expanded educational access for school dropouts by providing flexible learning opportunities that accommodate learners' social and economic conditions. The integration of Islamic educational values through moral guidance, religious activities, and character-based learning has strengthened learners' motivation, discipline, responsibility, and lifelong learning awareness. The implementation of the program is supported by community participation, institutional collaboration, and the commitment of educators, although limited infrastructure, learning facilities, and qualified tutors remain significant challenges. The novelty of this study lies in proposing an Islamic Education-Based Equivalency Education Model that integrates community empowerment, character education, and flexible non-formal learning as a comprehensive framework for preventing school dropout and promoting sustainable educational inclusion within community learning centers.